Crystal network structure and stability of beeswax-based oleogels with different polyunsaturated fatty acid oils - Hana, Wanjun; Chai, Xiuhang; Liu, Yuanfa; Xu, Yongjiang; Tan, Chin-Ping (Elsevier, 2022)
The effect of different types of oils including camellia oil (CLO), sunflower oil (SFO), corn oil (CO) and linseed oil (LO) on the formation, crystal network structure and mechanical properties of 4%wt beeswax (BW) in oleogel was investigated. BW oleogels containing oils with higher contents of polyunsaturated fatty acids gelled first (1%wt), especially LO with higher contents of linolenic acid rather than CLO with higher contents of monounsaturated fatty acids. In comparison, oils with higher polyunsaturated fatty acid contents exhibited higher Db with more extensive microstructure at different cooling rates, which was related to shorter nucleation induction time of crystal and higher crystallinity. Stronger van der Waals forces were observed in oleogels with higher polyunsaturated fatty acid contents especially for LO oleogel. Rheology also showed that LO oleogel with higher content of linolenic acid had higher crystallinity and lower crystal melting interfacial tension, resulting in the formation of a more stable network structure.